Tectonic Scenarios and Structural Deformation Patterns at the Northern end of the Wadi Araba Strike-slip Fault System, Jordan Plateau - Hseinat, Mu'ayyad Al; AlZidaneen, Malek (Geography, Earth Science and Environment: Research Highlights Vol. 2, 2024)
This chapter presents new insights into the deformational characteristics of the Wadi Shueib Structure (WSS) and the Amman-Halabat Structure (AHS) and their interaction with the regional tectonic framework of the Wadi Arab Strike-slip Fault (WAF). Utilizing Landsat-8 OLI imagery, lineament mapping was conducted through automated extraction, supported by digital image enhancement and principal component analysis (PCA) to refine lineament detection. Our findings reveal a higher density of lineaments along the main fault extensions of the WSS and AHS, with a lower density in areas covered by recent sediment deposits. Two dominant lineament trends (NE-SW and NW-SE) and a secondary trend (NNE-SSW) parallel the orientations of the WSS and AHS. In this study, two primary hypotheses have emerged to explain the forces driving the formation and evolution of deformation patterns within the AHF and WSF, as well as their connection to the WAF. The first hypothesis suggests that the AHF and WSF represent younger deformation phases that developed as horsetail structures following the formation of the WAF. The second hypothesis views them as pre-existing fault systems reactivated as restraining bends in response to the WAF’s evolution.